2023
DOI: 10.1038/s41598-023-33513-4
|View full text |Cite
|
Sign up to set email alerts
|

The neuropsychology of healthy aging: the positive context of the University of the Third Age during the COVID-19 pandemic

Abstract: Older adults have been reported to have increased susceptibility to the adverse effects of SARS-CoV-2 infection, such as fatal outcomes, cognitive decline, and changes in physical and/or mental health. However, few studies have examined neuropsychological changes by comparing measurements before and during the pandemic in healthy older people. In addition, no longitudinal studies have examined whether older adults may have responded positively to the pandemic. We examined these issues through a 2-year neuropsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Mental flexibility, with its cognitive-affective and physiological biomarkers, is a complex and multifaceted construct. Studying its components in healthy aging enables a better understanding of how they work and interact, as a signal of successful aging [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mental flexibility, with its cognitive-affective and physiological biomarkers, is a complex and multifaceted construct. Studying its components in healthy aging enables a better understanding of how they work and interact, as a signal of successful aging [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…After being administered the neuropsychological assessments, participants were exposed to a set of selected emotional images depicting events related to the lockdown COVID-19 pandemic, to assess individual differences in Affective Flexibility [ 59 ]. We randomly administered 75 pictures featuring emotional content associated with the pandemic situation [ 59 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a longitudinal neuropsychophysiological study published as part of this Collection examined University of the Third Age participants who continued to attend their learning classes and share their experiences via social media during the COVID-19 pandemic 16 . Neuropsychological data from before and during the pandemic showed that older people were able to maintain their cognitive ability if they continued to participate in social and educational activities.…”
mentioning
confidence: 99%
“…'Cognitive reserve' , accumulated over the lifespan, for example via education and other stimulating activities, may act as a buffer against cognitive impairment 10,11 . Cognitive reserve is associated with improved performance in global cognition, executive functions and attention 12,13 and has been shown to protect against brain damage and dementia, slow the cognitive aging process, and reduce the risk of psychiatric disorders 14,15 .Interestingly, a longitudinal neuropsychophysiological study published as part of this Collection examined University of the Third Age participants who continued to attend their learning classes and share their experiences via social media during the COVID-19 pandemic 16 . Neuropsychological data from before and during the pandemic showed that older people were able to maintain their cognitive ability if they continued to participate in social and educational activities.…”
mentioning
confidence: 99%